Copper (II) Ion-Modified Gold Nanoclusters as Peroxidase Mimetics for the Colorimetric Detection of Pyrophosphate - Shi, Yunjing; Wang, Jinjie; Mu, Kun; Liu, Suqin; Yang, Guang; Zhang, Min; Yang, Jingxia (Sensors (Basel, Switzerland), 2021)
Copper (II) ions have been shown to greatly improve the chemical stability and peroxidase-like activity of gold nanoclusters (AuNCs). Since the affinity between Cu2+ and pyrophosphate (PPi) is higher than that between Cu2+ and AuNCs, the catalytic activity of AuNCs-Cu2+ decreases with the introduction of PPi. Based on this principle, a new colorimetric detection method of PPi with high sensitivity and selectivity was developed by using AuNCs-Cu2+ as a probe. Under optimized conditions, the detection limit of PPi was 0.49 nM with a linear range of 0.51 to 30,000 nM. The sensitivity of the method was three orders of magnitude higher than that of a fluorescence method using AuNCs-Cu2+ as the probe. Finally, the AuNCs-Cu2+ system was successfully applied to directly determine the concentration of PPi in human urine samples.